Assessment of role of physical fitness of cricket players in response to the various tests - Smita Wagh,; Yatin Wagh,; Kamini D Nikam, (Asian Journal of Medical Sciences, 2022)
Background: Physical fitness is a very important aspect of cricket performance with physically prepared cricketers proven to perform better, more consistently, and with fewer injuries. The physical attributes of strength, speed, and endurance enable a cricketer to bat with power over long periods of time, bowl faster, and with greater accuracy, and to field athletically. Aim and Objectives: The present study was aimed to test the physical fitness of cricket players in response to the various tests administered for evaluation of different components of physical fitness. Materials and Methods: It was a cross-sectional analytical study conducted among 65 cricket players of a well-known cricket club in Mumbai. Physical fitness of cricketers was evaluated by measuring various health-related as well as skill-related fitness components. Results: Mean reading of balance in dominant leg of 37.25±9.8 s, while that in non-dominant leg as 21.65±8.9 s. We compared the results using unpaired “t”-test. Static balance of dominant leg is significantly higher as compared to non-dominant leg (P<0.01). Conclusion: The present study will be helpful to recognize level of fitness in each player and accordingly to organize and strengthen the cricket training program, to excel the performance, and also to avoid sport specific injuries in each cricketer.